The revised European social charter : an article by article commentary - Lukas, Karin; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2021)
"This detailed Commentary explores the boundaries of social rights at a European level through analysis of the Revised European Social Charter (RESC), the most comprehensive regional document on social rights. The Commentary considers the treaty as the counterpart of the European Convention on Human Rights, examining how it sets out fundamental rights in the social field. It focuses primarily on the rich jurisprudence developed by the Charter's monitoring body, the European Committee of Social Rights (ECSR). Key features include: discussion of the application of social rights in practice examination of the implementation of the RESC in national law a guide to social rights and the corresponding human rights obligations of European states that have ratified the Charter analysis of economic, social and cultural rights in Europe across a range of areas including housing, health, education, employment, legal and social protection, migration and non-discrimination. Contributing to a deeper understanding of how state authorities and other human rights actors apply social rights in Europe, this Commentary will be an essential resource for academics and students of European law and human rights. Its presentation and analysis of the case law of the ECSR will also be beneficial for practitioners, lawmakers and human rights activists"--
Foreword by manfred nowak -- Foreword by giuseppe palmisano -- Introduction -- Part I: General issues regarding the European social charter -- 1. The European social charter its history, application, procedures and impact -- 2. Methodology of the commentary -- Part II: Substantive provisions of the revised European social charter -- Article 1 the right to work -- Article 2 the right to just conditions of work -- Article 3 the right to safe and healthy working conditions -- Article 4 the right to a fair remuneration -- Article 5 the right to organise -- Article 6 the right to bargain collectively -- Article 7 the right of children and young persons to protection -- Article 8 the right of employed women to protection of maternity -- Article 9 the right to vocational guidance -- Article 10 the right to vocational training -- Article 11 the right to protection of health -- Article 12 the right to social security -- Article 13 the right to social and medical assistance ---Article 14 the right to benefit from social welfare services -- Article 15 the right of persons with disabilities to independence, social integration and participation in the life of the community -- Article 16 the right of the family to social, legal and economic protection -- Article 17 the right of children and young persons to social, legal and economic protection -- Article 18 the right to engage in a gainful occupation in the territory of other parties -- Article 19 the right of migrant workers and their families to protection and assistance -- Article 20 the right to equal opportunities and equal treatment in matters of employment and occupation without discrimination on the grounds of sex -- Article 21 the right to information and consultation -- Article 22 the right to take Part In the determination and improvement of the workingconditions and working environment -- Article 23 the right of elderly persons to social, legal and economic protection ---Article 24 the right to protection in cases of termination of employment -- Article 25 the right of workers to the protection of their claims in the event of the insolvency of their employer -- Article 26 the right to dignity at work -- Article 27 the right of workers with family responsibilities to equal opportunities and equal treatment -- Article 28 the right of workers' representatives to protection in the undertaking and facilities to be accorded to them -- Article 29 the right to information and consultation in collective redundancy procedures -- Article 30 the right to protection against poverty and social exclusion -- Article 31 the right to housing -- Part III: Selected procedural provisions of the revised European social charter -- Article e non-discrimination -- Article g restrictions -- Bibliography -- Index.
Obsahuje bibliografii, bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: European Social Charter -- (1961 říjen 18.); právo sociálního zabezpečení; sociální zabezpečení; sociální péče; sociální pomoc; social security law; social security; social care; social support; Evropa; Europe; e-knihy online; e-books online